2017
DOI: 10.1097/mph.0000000000000885
|View full text |Cite
|
Sign up to set email alerts
|

ACTN1-related Macrothrombocytopenia: A Novel Entity in the Progressing Field of Pediatric Thrombocytopenia

Abstract: We identified 11 patients with ACTN1-related macrothrombocytopenia diagnosed through pediatric probands. The aim was to underline the specificities of this entity, especially in children, and bring it to the knowledge of pediatricians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In 2013, six different mutations of ACTN1 were identified in 13 unrelated families with IMTP, which indicated that ACTN1 was one of the genetic lesions in IMTP (12). At present, thrombocytopenia caused by pathogenic variants in ACTN1 gene has been classified to ACTN1-related thrombocytopenia (15). To date, approximately 44 mutations of ACTN1 have been detected in IMTP patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, six different mutations of ACTN1 were identified in 13 unrelated families with IMTP, which indicated that ACTN1 was one of the genetic lesions in IMTP (12). At present, thrombocytopenia caused by pathogenic variants in ACTN1 gene has been classified to ACTN1-related thrombocytopenia (15). To date, approximately 44 mutations of ACTN1 have been detected in IMTP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Values for the red blood line were normal; however, there was a measureable increase in reticulocytes (18 promille, norm 3-13 promille) at the date of investigation. The father showed normal platelet count (209 x10 9 ) and mean platelet volume (10.5 fL). Platelet counts for the sisters of the IP (S1 and S2) were 84 x10 9 and 106 x10 9 , respectively.…”
Section: Case Presentationmentioning
confidence: 98%
“…The father showed normal platelet count (209 x10 9 ) and mean platelet volume (10.5 fL). Platelet counts for the sisters of the IP (S1 and S2) were 84 x10 9 and 106 x10 9 , respectively. Platelet size was not measurable in automatic cell count systems.…”
Section: Case Presentationmentioning
confidence: 98%
See 1 more Smart Citation
“…Mutations in the coding gene ( ACTN1 ) lead to macrothrombocytopenia and disorganization of the actin filaments because the formation of platelet precursor cells is disturbed. 39…”
Section: Introductionmentioning
confidence: 99%